Highly stable interface formation in onsite coagulation dual-salt gel electrolyte for lithium-metal batteries. Issue 9 (5th February 2021) - Lin, Yu-Hsing; Subramani, Ramesh; Huang, Yu-Ting; Lee, Yuh-Lang; Jan, Jeng-Shiung; Chiu, Chi-Cheng; Hou, Sheng-Shu; Teng, Hsisheng
Abstract : A polymeric framework of PVDF- co -HFP incorporated with PHEMA allows uniform Li plating/stripping on the anode. Abstract : The formation of Li dendrites in Li-metal batteries (LMBs) may lead to a short circuit, causing a fire or an explosion, and consume Li through dead-Li formation and solid-electrolyte interphase (SEI) thickening. Instead of using an artificial SEI, we use a gel polymer electrolyte (GPE) comprising poly(vinylidene fluoride- co -hexafluoro propylene) (PVDF- co -HFP) and poly(2-hydroxyethyl methacrylate) (PHEMA), dual lithium salts, and carbonate solvents to stabilize the SEI and suppress dendrite formation. When incorporated with a separator, the GPE exhibits higher ionic conductivity than liquid electrolytes and has a high Li + -transference number of 0.64. Without adding LiNO3, this GPE allows uniform Li plating/stripping on both Cu- and Li-metal anodes at high currents owing to robust SEI formation and negligible dendrite growth. Full-cell LMBs containing this GPE can deliver high capacities at high discharge rates and present high cycling stability. The high-polarity PVDF- co -HFP facilitates counter-ion dissociation to increase conductivity and tethers an anion to reduce the space-charge region and thus hinder Li-dendrite growth. Moreover, PHEMA closely contacts the metal anodes, which helps suppress solvent reduction and SEI thickening. This GPE is synthesized as a liquid, which coagulates onsite during LMB assembly. This study presents a strategy to advance metal anode technology for realizing LMBs.